Bus management system - Mohd Rahmat, Mohd Noordin (2005)
Bus Management System is an integrated electronic management system.This system ensure that the management process of this can company are smoothly done.This system will also help in decreasing error mostly cause by human mistake. This system was developed as one of the solution to transfer from current manual practices to a more systematic computerized system.This system will be developed by using Microsoft Visual Basic and Microsoft Access. Briefly there are two main modules for this system.The first module will be the Driver Management module and the second module will be Bus Management Module.However this thesis will just describe about Bus Management Module.In this module, the function that will be developed include,bus registration, maintenance record, and reminder.For this research, the case study been done in Transnasional Kuantan.